Looting – A New Analysis - Lane, Jan-Erik (Advances in Social Sciences Research Journal, 2022)
Looting typically stands for mass riots and civil unrest resulting in shop lensing. However, we can in a fruitful manner broaden the concept to include the management of embezzlement in the state. It is not the same as corruption. And it drives dictatorships.